2022
DOI: 10.32598/bcn.2021.2946.1
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Orexinergic System Within the Ventral Tegmental Area in the Development of Sensitization to Morphine Induced by Lateral Hypothalamus Stimulation

Abstract: The lateral hypothalamus (LH) has long been known to implicate in the addictive behaviors of drugs of abuse. The ventral tegmental area (VTA) is a major area of the mesolimbic system that is strongly involved in the development of morphine sensitization. The current study aimed to examine the role of intra-VTA orexin receptors in the LH stimulation-induced sensitization to the antinociceptive response of morphine. One hundred fourteen adult male Wistar rats underwent unilateral implantation of two separate can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The orexin projections are involved in various behavioral and physiological functions (Sakurai, Amemiya et al ., 1998; Marcus, Aschkenasi et al ., 2001; Sargin, 2019). Previous studies showed orexin receptors are located in the lateral hypothalamic and thalamic nuclei (Haghparast, Fatahi et al ., 2017; Salehi, Kashfi et al ., 2020), locus coeruleus (Safari, Haghparast et al ., 2009, 2011), nucleus accumbens (NAc) (Yazdi, Jahangirvand et al ., 2016; Andreoli, Marketkar et al ., 2017), ventral tegmental area (VTA) (Sadeghi, Reisi et al ., 2013; Ezzatpanah, Babapour et al ., 2016; Haghparast and Rashvand, 2022), hippocampus (Haghparast, Fatahi et al ., 2017; Haghparast, Shafiei et al ., 2018; Brojeni, Rashvand et al ., 2019; Rasouli, Rashvand et al ., 2020; Zargarani, Karimi-Haghighi et al ., 2021), basal ganglia, cerebral cortex, preoptic area, reticular formation (Cluderay, Harrison et al ., 2002; Razavi and Hosseinzadeh, 2017). Indeed, several studies have shown that the orexin system plays an essential role in reward-seeking behaviors (Haghparast, Fatahi et al ., 2017; Zarrabian, Riahi et al ., 2020), sensory modulation (Sakurai, 2014; Andreoli, Marketkar et al ., 2017; Park and Weon, 2017), stress processing (Grafe and Bhatnagar, 2018; Sargin, 2019), endocrine functions (Martyńska, Polkowska et al ., 2006), and pain modulation (Chiou, Lee et al ., 2010; Askari, Oryan et al ., 2021; Li, Chang et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The orexin projections are involved in various behavioral and physiological functions (Sakurai, Amemiya et al ., 1998; Marcus, Aschkenasi et al ., 2001; Sargin, 2019). Previous studies showed orexin receptors are located in the lateral hypothalamic and thalamic nuclei (Haghparast, Fatahi et al ., 2017; Salehi, Kashfi et al ., 2020), locus coeruleus (Safari, Haghparast et al ., 2009, 2011), nucleus accumbens (NAc) (Yazdi, Jahangirvand et al ., 2016; Andreoli, Marketkar et al ., 2017), ventral tegmental area (VTA) (Sadeghi, Reisi et al ., 2013; Ezzatpanah, Babapour et al ., 2016; Haghparast and Rashvand, 2022), hippocampus (Haghparast, Fatahi et al ., 2017; Haghparast, Shafiei et al ., 2018; Brojeni, Rashvand et al ., 2019; Rasouli, Rashvand et al ., 2020; Zargarani, Karimi-Haghighi et al ., 2021), basal ganglia, cerebral cortex, preoptic area, reticular formation (Cluderay, Harrison et al ., 2002; Razavi and Hosseinzadeh, 2017). Indeed, several studies have shown that the orexin system plays an essential role in reward-seeking behaviors (Haghparast, Fatahi et al ., 2017; Zarrabian, Riahi et al ., 2020), sensory modulation (Sakurai, 2014; Andreoli, Marketkar et al ., 2017; Park and Weon, 2017), stress processing (Grafe and Bhatnagar, 2018; Sargin, 2019), endocrine functions (Martyńska, Polkowska et al ., 2006), and pain modulation (Chiou, Lee et al ., 2010; Askari, Oryan et al ., 2021; Li, Chang et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%